2016
DOI: 10.1002/ejic.201501480
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Steroidal Anti‐Inflammatory Drugs (NSAIDs) in Metal Complexes and Their Effect at the Cellular Level

Abstract: The nonsteroidal anti-inflammatory drugs (NSAIDs) make up a great group of drugs that provide benefits in the prevention of cancers. Coordinated metal ions with NSAIDs provide advantages over the drugs themselves. The metal complexes of NSAIDs display a range of biological activities quite often inaccessible to the original NSAID ligands. NSAIDs-metal complexes have molecular properties different from those of the parent drugs. Thus, if a given NSAIDs-metal complex remains intact in the biological medium its b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(66 citation statements)
references
References 102 publications
(203 reference statements)
0
62
0
4
Order By: Relevance
“…Nonsteroidal anti‐inflammatory drugs (NSAIDs) are the most prescribed drugs in the world as an analgesic, anti‐inflammatory and anti‐inflammatory agents . NSAIDs are responsible for the inhibition of the cyclooxygenase (COX) enzyme (COX‐1 and COX‐2).…”
Section: Introductionmentioning
confidence: 99%
“…Nonsteroidal anti‐inflammatory drugs (NSAIDs) are the most prescribed drugs in the world as an analgesic, anti‐inflammatory and anti‐inflammatory agents . NSAIDs are responsible for the inhibition of the cyclooxygenase (COX) enzyme (COX‐1 and COX‐2).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have also provided evidence that aspirin promotes deoxyribonucleic acid (DNA) self-healing by the upregulation of hMLH1, hMSH2, hMSH6, hPMS2 [43], and XRCC expression [44], slowing down gene-mutation accumulation, and protecting normal cell DNA [32,45]. Recent studies have suggested several new aspirin pathways, such as inhibiting the synthesis of prostaglandin E2 (PGE2) [46], controlling the number of circulating platelets and their activity levels to evade several innate anti-tumor effects [47][48][49][50], increasing chemo-agent toxicity, and downregulating cellular drug resistance [51,52]. Since the results of these basic studies have mostly been conducted in vitro and have not been proven in humans, these outcomes cannot be presented as definitive mechanisms of aspirin's effects.…”
Section: Discussionmentioning
confidence: 99%
“…[38,39] Some studies have also provided evidence that aspirin promotes DNA self-healing by the upregulation of hMLH1, hMSH2, hMSH6, hPMS2, [40] and XRCC expression, [41] slowing down gene mutation accumulation, and protecting normal cell DNA. [29,42] Recent studies have suggested several new aspirin pathways, such as inhibiting the synthesis of PGE2, [43] controlling the number of circulating platelets and their activity levels to evade several innate anti-tumor effects, [44][45][46][47] increasing chemo agent toxicity, and downregulating cellular drug resistance. [48,49] Since the results of these basic studies have mostly been conducted in vitro and have not been proven in humans, these outcomes cannot be presented as definitive mechanisms of aspirin.…”
Section: Discussionmentioning
confidence: 99%